2010
DOI: 10.1093/jpepsy/jsq048
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Victimization from Five Subtypes of Bullying: Physical, Verbal, Social Exclusion, Spreading Rumors, and Cyber

Abstract: Increased co-occurrence of victimization types put adolescents at greater risks for poorer physical and psychological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
175
3
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(203 citation statements)
references
References 22 publications
15
175
3
10
Order By: Relevance
“…Among the victims of physical aggressions, most were males, confirming the findings of other authors who have identified greater involvement of males [19,[22][23][24][25]. One suggested explanation is that the stereotypical participation of boys and girls in situations of bullying has social roots, because traditionally the more aggressive behavior and violence of boys are reinforced, whereas indirect involvement or further victimization of girls is more consistent with traditional stereotypes of femininity [26].…”
Section: Discussionsupporting
confidence: 81%
“…Among the victims of physical aggressions, most were males, confirming the findings of other authors who have identified greater involvement of males [19,[22][23][24][25]. One suggested explanation is that the stereotypical participation of boys and girls in situations of bullying has social roots, because traditionally the more aggressive behavior and violence of boys are reinforced, whereas indirect involvement or further victimization of girls is more consistent with traditional stereotypes of femininity [26].…”
Section: Discussionsupporting
confidence: 81%
“…Table 2 about here A robust Mokken scale must be relatively immune to variables potentially related to the subject of the scale. The first relevant variable here is gender: Boys or men experience other and more severe types of violence than girls or women (Marshall, 1992;Regan et al, 2006;Wang et al, 2010). Furthermore, the variables country of birth and feeling at home in the country in which one is actually living are shown to be important for the experience of violence in and around school (Beauvais & Jenson, 2002;Felix et al, 2009).…”
Section: Variablesmentioning
confidence: 99%
“…National and international studies highlight the consequences of bullying in the short and long term in the lives of children and adolescents who experience this situation [11][12][13] , interfering in cognitive and socioemotional development, whether as victims, aggressors, or even spectators of such events. When suffering bullying, children and adolescents are more exposed to difficulty concentrating, low self-esteem, anxiety, depression, suicidal ideation, attempted suicide, consummate suicide, self-harm, and psychological stress [12][13][14][15][16][17] . A study developed in the countryside in Southeast Brazil identified that adolescents who are victims of bullying present emotions such as feelings of anger, discouragement, sadness, and shame 11 .…”
Section: Introductionmentioning
confidence: 99%